LINGUPOETICS IN THE WORKS AND WORKS OF TUGAY MUROD - Gayratova Gulzoda Sanat daughter (International Journal of Innovations in Engineering Research and Technology, 2021)
The peculiarity of the current stage of development of our literature is that it conducts a wide range of philosophical and moral-spiritual research. It is safe to say that the artistic expression of such spiritual and moral values occurs not only because of the spiritual needs of the people, but also as a spiritual need of literature. It is especially gratifying that Uncle Murad's creative research is based on colorful life materials. Because: “As long as a writer creates images and characters of life events, he cannot remain a slave to his imagination. There are certain forces that determine the direction of the pen that go beyond the wishes of the writer, and the artist cannot ignore them. One of them is the logic of life.